A new species of Glochinomyia Kertész from Papua New Guinea (Diptera: Stratiomyidae, Pachygastrinae) - Rozkošný, Rudolf (Zootaxa, 2013)
Glochinomyia nigriseta sp. nov. is described and illustrated. The generic characters of Glochinomyia are summarized and the new species is compared with the description of the only known species, G. albiseta Kertész. The taxonomic position of Glochinomyia is briefly discussed and the Papuan species of the Pachygastrinae with four scutellar spines are keyed.